Impact of COVID-19 pandemic on education: Moving towards e-learning paradigm - Ammar Odeh; Ismail Keshta (Institute of Advanced Engineering and Science, 2022)
Besides the economic impact and loss of jobs and revenues, COVID-19 have a great impact on the education sector, with several learning institutions across the world remaining shut down for months. This study evaluated the impact of COVID-19 pandemic on education. The study employed a cross-sectional study design in which data was collected using qualitative methods from various education stakeholders as well as secondary literature. The result showed that learning has severely been affected by the strict protocols adopted by various governments in response to COVID-19 pandemic. The major responses to COVID-19 like closing up schools have left most learners hopeless as they cannot afford the recommended online learning. The major responses to COVID-19 at the few operating schools include: wearing masks, hand sanitization, regular hand washing, constant temperature check for both staff and learners, and lastly change on the sitting arrangements as students are required to maintain a social distance of at least 1.5 meters. Moreover, closure of schools has also had a severe impact on the co-curricular activities that are always undertaken within the academic institutions like athletics, drama and ball games. Measures should be put in place by various governments to ensure that all learners have access to equitable, quality and inclusive forms of education during the present COVID-19 pandemic.